Singapore takes six steps forward in 'The Quality of Death Index' Rankings - Stella Seow Lin Goh (Elsevier, 2018)
In the latest 2015 Quality of Death Index, Singapore managed to move SIX steps forward from 18th to the 12th position. This advancement has been hard-won, with victories to improve the level of palliative care such as creating awareness of palliative service, improving coordinated care and growing an adequate capacity to meet the demand of care in our fast -growing ageing population. But it hasn't always been easy. Despite being a first world country, Asian societies like Singapore have inherited taboos regarding public dialogue about death and dying. Such dialogue is traditionally avoided. However, through years of continual effort in improving the standard of palliative care delivery, redesigning education module, creating public awareness and improving funding system, Singapore's palliative care providers have improved the lives of those with life-limiting illnesses. Nevertheless, the government will continue to improve and work toward achieving single digits in the next ranking of the Quality of Death Index.